A Hydrophobic antireflective and antidust coating with $\text{SiO}_2$ and $\text{TiO}_2$ nanoparticles using a new 3-D printing method for photovoltaic panels - EKREN, NAZMİ; SAĞLAM, ŞAFAK (My University, 2022)
The main outdoor factors that reduce the efficiency of the photovoltaic (PV) panel are the reflection and refraction of light, dirt, dust, and organic waste accumulating on the panel surface. In this article, an antireflection, self-cleaning coating was applied on the PV panel cover glass with a new method. With the coating, the surface has been given a hydrophobic feature. As a coating method, a 3-D printer has not been seen in the literature and used as a new method. The electrospinning method has also been tried as an alternative method. Solutions in different combinations were developed using polylactic acid or polymethylmethacrylate polymer, chloroform ($\text{CHCl}_3$) as a solvent, and silicon dioxide ($\text{SiO}_2$) and titanium dioxide ($\text{TiO}_2$) nanoparticles as primary materials in a modified 3-D printer for bioprinting. Five PV panels were obtained by applying different 3-D parameters from three solutions, which have the best results. Coating thicknesses are in the range of 3.12-8.47 mu m. Coated and uncoated PV panels were tested in outdoor conditions for ten-day periods. The power outputs of the PV panels were measured, and their ten-day average efficiency was presented. According to the results, the highest efficiency increase is 8.7%. The highest light transmittance is 88.2% at 550 nm. In addition, hydrophobic properties were observed on all surfaces and the water contact angle was measured as 96.18 degrees.
Keywords: Tarımsal Bilimler; Ziraat; Tarım Makineleri; Tarımda Enerji; Biyoyakıt Teknolojisi; Fizik; Temel Bilimler; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Farm Machinery; Energy in Agriculture; Biofuels Technology; Physics; Natural Sciences; Engineering and Technology; ENERJİ VE YAKITLAR; Mühendislik; Mühendislik, Bilişim ve Teknoloji (ENG); MALZEME BİLİMİ, ÇOKDİSİPLİNLİ; Malzeme Bilimi; FİZİK, UYGULAMALI; Temel Bilimler (SCI); ENERGY & FUELS; ENGINEERING; Engineering, Computing & Technology (ENG); MATERIALS SCIENCE, MULTIDISCIPLINARY; MATERIALS SCIENCE; PHYSICS, APPLIED; PHYSICS; Natural Sciences (SCI); İstatistiksel ve Doğrusal Olmayan Fizik; Metaller ve Alaşımlar; Malzeme Kimyası; Genel Malzeme Bilimi; Genel Mühendislik; Mühendislik (çeşitli); Yenilenebilir Enerji, Sürdürülebilirlik ve Çevre; Yakıt Teknolojisi; Enerji Mühendisliği ve Güç Teknolojisi; Enerji (çeşitli); Genel Enerji; Fizik Bilimleri; Statistical and Nonlinear Physics; Metals and Alloys; Materials Chemistry; General Materials Science; General Engineering; Engineering (miscellaneous); Renewable Energy, Sustainability and the Environment; Fuel Technology; Energy Engineering and Power Technology; Energy (miscellaneous); General Energy; Physical Sciences; Coatings; Glass; Printers; Surface treatment; Programmable logic arrays; Printing; Solvents; 3-D printing; antireflection; hydrophobic; nanoparticle; photovoltaic (PV); self-cleaning; SOL-GEL; TRANSPARENT; FABRICATION; POLYMERS; SURFACES